2-OHOA supplementation reduced adiposity and improved cardiometabolic risk to a greater extent than n-3 PUFA in obese mice. Issue 6 (November 2019) - Redondo Useros, Noemí; Gheorghe, Alina; Perez de Heredia, Fátima; Díaz, Ligia E.; Baccan, Gyselle Chrystina; De la Fuente, Mónica; Marcos, Ascensión
Highlights: 2-OHOA reduced body weight, plasma leptin, blood pressure and triglycerides in obese mice. 2-OHOA partially restored adiponectin and resistin secretion in adipocytes. N-3 PUFA only reduced triglycerides in obese mice. Leptin showed positive correlations to cardiovascular risk biomarkers. Abstract: Objective: We aimed to assess whether 2-hydroxyoleic acid (2-OHOA) and n-3 polyunsaturated fatty acids (PUFA) could counteract changes on adipokine secretion and cardiometabolic risk biomarkers associated with high-fat diet-induced obesity in mice. Methods: Female ICR/CD1 mice (8 weeks old) were divided into four groups receiving different diets (n = 8/group): (1) standard chow (control) for 18 weeks; (2) 22% fat for 4 weeks + 60% fat for 14 weeks (obesogenic diet, OD); 3) OD + 2-OHOA (1500 mg kg −1 diet) for the last 6 weeks (ODHO); and 4) OD + n-3 PUFA (eicosapentaenoic + docosahexaenoic acids, 1500 + 1500 mg kg −1 diet) for the last 6 weeks (OD-N3). After 18 weeks, body weight, periovarian visceral fat, heart and liver weights were measured, as well as cardiometabolic parameters (systolic and diastolic blood pressure, blood glucose, insulin, HOMA index, triglycerides, total cholesterol, apolipoproteins A1 and E), plasma adipokines and inflammatory proteins (leptin, adiponectin, plasminogen activator inhibitor 1 [PAI1], soluble E-selectin [sE-selectin], matrix metalloproteinase-9 [MMP-9], fibrinogen, soluble intercellular adhesion molecule [sICAM] and soluble vascular adhesion molecule [sVCAM]), and secretion of pro-inflamatory cytokines and inflammatory biomarkers from periovarian adipocytes. Results: OD mice had greater body and heart weights, and plasma leptin, and lower adiponectin and resistin secretion from adipocytes. Supplementation with 2-OHOA reduced body and heart weights, blood pressure, triglycerides and leptin, and restored adiponectin and resistin secretion, while n-3 PUFA only reduced triglyceride levels (all P < 0.05). Conclusion: 2-OHOA supplementation was more effective in reducing adiposity, modulating adipokine secretion and ameliorating cardiometabolic risk than n-3 PUFA.